2017
DOI: 10.9790/0837-2201067580
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Academic Self-efficacy Believed of College Students and Academic Performance.

Abstract: :-This paper investigate the levels of students' academic self-efficacy beliefs and relationship between academic self-efficacy with students' academic performance among final year students' in one of Nigerian Colleges of education. Questionnaire was used as the means of data collection. A total sample of 339 respondents who were stratified and randomly selected from five faculties of the College participated in the research. The respondents were between the age of 19 to 34 years old with mean age equals 23.19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…Students with high self-efficacy preferred mastery goals, which entailed challenges and new knowledge, as well as performance goals that comprised good grades and surpassing others (Köseoglu, 2015). Students' should be exposing to the kind of self-efficacy intervention program in order for the students' to be having a kind of confidence to feel that, they can really perform well and deal with all academic related task positively, which in turn improve academic achievement of students' positively (Kolo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Students with high self-efficacy preferred mastery goals, which entailed challenges and new knowledge, as well as performance goals that comprised good grades and surpassing others (Köseoglu, 2015). Students' should be exposing to the kind of self-efficacy intervention program in order for the students' to be having a kind of confidence to feel that, they can really perform well and deal with all academic related task positively, which in turn improve academic achievement of students' positively (Kolo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…If it is not provided they are discouraged and their emotional wellbeing is affected. Their emotional and physiological state is associated with fruitful outcomes as good results are always encouraging for them and bad results shaken their affective aspects of personality (Kolo et al, 2017). Yokoyama (2019, p.2) has similar views as he concludes in his meta-analysis study, "self-efficacy can be strengthened of mastery, observing someone succeed, social persuasion such as direct encouragement.…”
Section: Literature Reviewmentioning
confidence: 98%
“…According to Bandura, (1997, p.115),"efficacy beliefs are the product of cognitive processing of diverse sources of efficacy information conveyed enactively, vicariously, socially and physiologically." Although various research studies have reported their overall impact differently as few interpret mastery experience as more powerful source while others consider emotional state more strong predictor of efficacy (Kolo et al, 2017).According to Gao (2020, p.715), "students not only experience different degrees of exposure to the sources of self-efficacy but also hold diverse viewpoints of influence of each source on their self-efficacy. "…”
Section: Literature Reviewmentioning
confidence: 99%
“…Efikasi diri ini dapat mempengaruhi prestasi akademik seorang siswa. Efikasi diri dan prestasi akademik memiliki hubungan yang positif saat pembelajaran kimia berlangsung (Kolo et al, 2017). Pencapaian belajar siswa dengan efikasi diri yang tinggi akan lebih baik daripada siswa dengan kemampuan yang sama namun memiliki efikasi diri yang lebih rendah (Zimmerman et al, 1992).…”
Section: Pendahuluanunclassified